2006
DOI: 10.1021/ol052994+
|View full text |Cite
|
Sign up to set email alerts
|

One-Step, Three-Component Synthesis of Pyridines and 1,4-Dihydropyridines with Manifold Medicinal Utility

Abstract: Privileged medicinal scaffolds based on the structures of 2-amino-3,5-dicyano-6-sulfanylpyridines and the corresponding 1,4-dihydropyridines have been prepared via a single-step, three-component reaction of structurally diverse aldehydes with various thiols and malononitrile. Mechanistic studies revealed that 1,4-dyhidropyridines undergo oxidation by the intermediate Knoevenagel adducts rather than by air oxygen. Although the latter process undermines the yields of pyridines, it results in the formation of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(78 citation statements)
references
References 21 publications
3
71
1
Order By: Relevance
“…Hence there is a necessity to develop newer, greener, effective and environmental friendly methods of synthesis of poly substituted pyridine derivatives. It is further observed that in the above reported methods [18][19][20][21][22][23] thiophenol has been used as a reactant but substituted phenolic derivatives such as 2-amino-6-phenoxy-pyridine-3, 5-dicarbonitrile derivatives have not been reported.…”
Section: Research Articlementioning
confidence: 99%
“…Hence there is a necessity to develop newer, greener, effective and environmental friendly methods of synthesis of poly substituted pyridine derivatives. It is further observed that in the above reported methods [18][19][20][21][22][23] thiophenol has been used as a reactant but substituted phenolic derivatives such as 2-amino-6-phenoxy-pyridine-3, 5-dicarbonitrile derivatives have not been reported.…”
Section: Research Articlementioning
confidence: 99%
“…However, one-pot, three-component condensation between aldehyde, malononitrile, and thiol has been the most exploited pathway. This multicomponent condensation has been delineated to proceed via Knoevenagel-thiaMichael cascade pathway (Scheme 1b;19,20). As Knoevenagel as well as Michael addition reactions are usually catalyzed by bases, a range of bases such as Et 3 N, DABCO (20,21), piperidine, TBAH (22), DBU (23), {(bmim) OH} (24), KF-Al 2 O 3 (25), nanocrystalline-MgO (26), ethanolic KOH (27), K 2 CO 3 -KMnO 4 (28), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the synthesis of highly substituted pyridines has attracted much attention, and a number of procedures have been developed using a variety of protocols, such as hetero-Diels-Alder reaction of 3-siloxy-1-aza-1,3-butadienes with electron-deficient acetylenes [8], three-component condensation of aldehyde, malononitrile, and thiol [9], ruthenium-catalyzed cycloisomerization of 3-azadienynes [10], Mannich reaction of aldehydes and iminium salts [11] and Vilsmeier-Haack reaction of Rhydroxyketenedithioacetals [12]. Among these, one of the very convenient approaches which attracted our attention is the three-component condensation of aldehyde, malononitrile, and thiol to the highly substituted pyridines developed by Evdokimov et al [9]. Herein, we report a mild, practical and highly efficient procedure for the preparation of the title compounds using nanoTiO 2 catalyst at room temperature (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%